Analysis of Factors Associated with the Incidence of Dengue Fever - ST Sufiati; Irfansyah Baharuddin Pakki; Ratih Wirapuspita (GLOBAL HEALTH SCIENCE GROUP, 2026)
Dengue Hemorrhagic Fever (DHF) remained a public health problem in Bontang City. From January to December 2023, a total of 457 DHF cases were reported among 188,101 residents, with an incidence rate of 242.95 per 100,000 population and two deaths (Case Fatality Rate = 0.44%). This study aimed to identify factors associated with the occurrence of Dengue Hemorrhagic Fever in the working area of Bontang Barat Public Health Center. An analytic observational study with a retrospective case control design was conducted. The study population consisted of all DHF cases reported from January to December 2023, totaling 128 cases. Using simple random sampling, 192 respondents were selected, comprising 96 cases and 96 controls. Cases were patients with dengue hemorrhagic fever (DHF) confirmed by healthcare professionals, while the control group consisted of neighbors of the cases who agreed to participate and were matched by sex and residential area (±100 m). Data were collected from DHF surveillance records, interviews, observations, and measurements of housing density. Data were analyzed using the Chi-square test. The results showed a significant association between 3M Plus practices, the presence of mosquito larvae (p < 0.001), and the frequency of cleaning water storage containers (p = 0.001) with the occurrence of DHF. In contrast, housing density (p = 0.721) and the habit of hanging worn clothes (p = 0.771) were not associated with DHF incidence. Conclusion the occurrence of DHF was mainly influenced by behavioral and environmental factors therefore, strengthening community based 3M Plus prevention practices was identified as a key strategy for DHF control.